2017
DOI: 10.1104/pp.17.01234
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Fluctuating Light on Crop Performance

Abstract: Rapidly changing light conditions can reduce carbon gain and productivity in field crops because photosynthetic responses to light fluctuations are not instantaneous. Plant responses to fluctuating light occur across levels of organizational complexity from entire canopies to the biochemistry of a single reaction and across orders of magnitude of time. Although light availability and variation at the top of the canopy are largely dependent on the solar angle and degree of cloudiness, lower crop canopies rely m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
176
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 130 publications
(170 reference statements)
2
176
1
8
Order By: Relevance
“…The irradiance and temperature conditions required to induce photoprotection, or cause photodamage in plants is complex, as are the conditions determining the dynamics and magnitude of the recovery process. Both induction and recovery are dependent upon a myriad of additional factors, for example leaf angle, leaf orientation, leaf canopy position, the proportion of direct and diffuse irradiance, the recent irradiance and temperature to which the plants have acclimated, season and leaf age (Bongi & Long, 1987;Long et al, 1994;Garbulsky et al, 2011;Williams et al, 2014;Wong & Gamon, 2015a,b;Slattery et al, 2018). The dynamics of recovery are highly variable, ranging from rapid (min to h) recovery from photoprotection or prolonged (days) depression of photosynthetic performance following severe photodamage (Bolharnordenkampf et al, 1991;Farage & Long, 1991;Groom & Baker, 1992;Ogren & Evans, 1992;Long et al, 1994;Zhu et al, 2004;Takahashi & Murata, 2008;Kromdijk et al, 2016;Slattery et al, 2018).…”
Section: (B) (A)mentioning
confidence: 99%
“…The irradiance and temperature conditions required to induce photoprotection, or cause photodamage in plants is complex, as are the conditions determining the dynamics and magnitude of the recovery process. Both induction and recovery are dependent upon a myriad of additional factors, for example leaf angle, leaf orientation, leaf canopy position, the proportion of direct and diffuse irradiance, the recent irradiance and temperature to which the plants have acclimated, season and leaf age (Bongi & Long, 1987;Long et al, 1994;Garbulsky et al, 2011;Williams et al, 2014;Wong & Gamon, 2015a,b;Slattery et al, 2018). The dynamics of recovery are highly variable, ranging from rapid (min to h) recovery from photoprotection or prolonged (days) depression of photosynthetic performance following severe photodamage (Bolharnordenkampf et al, 1991;Farage & Long, 1991;Groom & Baker, 1992;Ogren & Evans, 1992;Long et al, 1994;Zhu et al, 2004;Takahashi & Murata, 2008;Kromdijk et al, 2016;Slattery et al, 2018).…”
Section: (B) (A)mentioning
confidence: 99%
“…Long‐term light fluctuations include changes in weekly weather conditions and even seasonal variation, which affect plant development and photosynthetic efficiency. Recent insights into mismatches between incoming light and the ability to put that energy into use in carbon assimilation as a result of light fluctuations showed that these can cause considerable growth penalties and reduction in photosynthetic carbon assimilation in photoautotrophic organisms (Zhu et al ., ; Graham et al ., ; Vialet‐Chabrand et al ., ; Taylor and Long, ; Morales et al ., ; Slattery et al ., ). This has been further demonstrated in Arabidopsis plants that lack functional genes involved in photoprotection and light adaptation, such as in the PsbS npq4‐1 (Li et al ., ) and glucose 6‐phosphate / phosphate translocator 2 ( gpt2 ) (Athanasiou et al ., ) mutants.…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 97%
“…Decreasing leaf chlorophyll content to allow more radiation into the canopy is a possible route to improving canopy photosynthetic efficiency (Ort et al ., , ). This should result in minor reductions in overall photosynthetic efficiency while significantly saving on nitrogen input (Slattery et al ., ; Walker et al ., ). Therefore, this trait has received considerable attention in GWAS (Dhanapal et al ., ; Hao et al ., ; Lin et al ., ; Wang et al ., ).…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 99%
“…Two must-read Updates on photosynthetic dynamics caused by fluctuations in irradiance review the salient physiology and promising strategies for improving photosynthesis in crop canopies (Kaiser et al, 2018;Slattery et al, 2018). One possible strategy is to optimize the use of sunflecks within the lower part of the canopy.…”
Section: Photosynthesis: Maximizing Flexibility and Outputmentioning
confidence: 99%